The Effect of Specialized Exercises on Some Kinematic Variables and Targeted Stages of Performance in Youth Discus Throwers (Damu Journal of Sport Sciences, 2025)
This study aims to examine the effect of special exercises on certain kinematic variables and targeted performance phases for youth discus throwers. A set of exercises was designed based on scientific principles and biomechanical analysis of the thrower's movement, with the goal of improving technical performance efficiency and increasing throwing distance.These exercises were applied to a sample of youth discus throwers, and several kinematic variables were measured, including angular velocity, support time, center of mass trajectory, and body angles during execution. The results showed a significant improvement in these variables, positively reflecting on the athletes' performance levels.The study recommends integrating these special exercises into training programs for youth discus throwers, as they play an effective role in enhancing performance and achieving better competition results.